Factors Contributing to Students' Sleep Quality at SMKN 1 Narmada in 2024 - Moh. Arip; Dewi Purnamawati; Muhammad Hasbi; Sahrir Ramadhan; Nani Ewi Salman (Green Publisher Indonesia, 2025)
Decreased sleep quality is something that is often found and continues to increase every year throughtout the world. Adolescents are an age group that often has poor sleep quality. Poor sleep quality can disrupt psycho and physiological balance. The aim of this research is determine the factors that contribute to the quality of sleep of students at SMKN 1 Narmada. This research method uses a cross sectional design with proportionate stratified random sampling. The number of samples is 84 students. The dependent variable in this study is sleep quality, while the independent variables are age, gender, helath status, stres, coffe consumption, smoking, environment and screen time. The data was processed desriptively and presented in the form of a frequency distribution table. The research results obtained were that the sleep quality of the dominant respondents in the bad category was 61 people (72,6%). The factors that contribute to students sleep quality are health status (ρ=0,046), stress (ρ=0,027), coffe (ρ=0,030) and and screen time (ρ=0,000) while factors that do not contribute to quality students sleep quality are age (ρ=0,421), gender (ρ=0,258), smoking (ρ=0,713), and environment (ρ=0,178). Screen time is the most dominan factor with an Exp (ꞵ) value of 7,546. The conclusion is that there is a relationship between health status, stres, coffe consumption and screen time with student`s sleep quality while age, gender, smoking and environment factors have no relationship with student`s sleep quality.